Study on ω-fatty acids from Malaysian giant mudskipper (Periophthalmodon schlosseri) fish oil - Omar, Muhammad Nor; Che Othman, Siti Fairuz; Mohamad Talib, Hasan; Muhd Nor, Nor Nazuha; Muhd Nor, Nor Dalilah; Yunus, Kamaruzzaman (Oriental Scientific Publishing Co., 2010)
The main aim of the present study is to look into the composition of Malaysian giant mudskipper lipid which might be useful to human health by looking into the ratio of ω-fatty acids present in P.schlosseri oil. Lipid from the fish flesh was extracted using the Folch method and the fatty acid composition was analysed using GC and GC-MS. It was found that the major constituents of P. schlosseri lipid were palmitic acid (C16:0) (29.2%), oleic acid (C18:1 ω-9) (23.0%) and stearic acid (C18:0) (12.6%). Besides that, the essential ω-fatty acids eicosapentaenoic acid (EPA, C20:5, ω-3) and docosahexaenoic acid (DHA, C22:6, ω-3) contents were 3.3 and 4.3% respectively. The result shows that the total ω-fatty acid (ω-3 and ω-6) content of P. schlosseri was 15.4% and is nutritionally significant due to its ω-3:ω-6 ratio of 1:1.